Сравнительный анализ графических методов проектирования информационных систем - Валькман, Ю.Р.; Ланбина, А.В.; Потапчук, Е.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
This article represents a graphical methods for structural and object-
oriented approach, the software analyzed. Given their comparative analysis.
Recommended for software develop, analyze and restructuring.